DEGRADAÇÃO DE CORANTES E TRATAMENTO DE EFLUENTE TÊXTIL POR PROCESSO REDUTIVO UTILIZANDO LÃ DE AÇO COMERCIAL SEGUIDO DE PROCESSO OXIDATIVO - Figueiredo, Ana Carolina Ferreira (2019)
Textile industries stand out as one of the most polluting industries, mainly regarding to water pollution. It is also among the main water-using industries (> 100 L kg-1 of fabric produced) and, consequently, it generates a large amount of effluent (250 to 350 m3 ton- 1 of final product). The generated effluent presents a complex and variable composition and an intense color due to the presence of dyes. Conventional treatment systems generally adopted by the textile industries are inefficient for effective degradation of these compounds. Therefore, the present study proposes the combination of reduction process using commercial steel wool as a source of metallic iron (Fe0) with oxidative processes aiming dyes (Reactive 19, Reactive Orange 16, Reactive Black 5) degradation and textile effluent treatment. Initially, it was studied the effect of the predictive variables (pH and steel wool mass) on the reductive process for dyes and textile effluent discoloration by a full factorial design (32). Applying the process at pH 7 and using 10 g of steel wool, after 45 minutes it was possible to achieve 40% of reduction of the total spectral area and 70% of reduction of the dye color. By the generation of 15 mg L-1 of soluble iron in the reductive process, the combination with photo-Fenton oxidative process allowed to obtain almost the complete removal of intermediate compounds and the complete removal of residual dyes color, after 30 minutes. In the treatment of textile effluent using a batch system, after 30 minutes the reductive process performed in natural pH (pH 7 and 8 g of steel wool) provided reductions of 54% of COD, 78% of TOC, 37% of true color and 58% of total phenols of the textile effluent; in the other hand, using a continuous flow system the reduction process allowed a removal of 68% of COD, 46% of TOC, 62% of true color and 72% of total phenols of the textile effluent. However, it presented as inconvenient an increase in the apparent color and turbidity of the effluent, due to the iron species that are formed from the oxidation of steel wool during the process. The combined processes showed to be an efficient alternative to obtain a suitable effluent regarding to COD, total phenols and true color removal in order to disposal the effluent in a water body in accordance with environmental laws. Acute toxicity studies using the biological indicator Daphnia magna proved the elimination/reduction of the textile effluent toxicity after reduction and combined process. Although all the studies have been carried out in a laboratory scale, the results suggest that the reductive process combined with oxidative process can be considered an efficient alternative. It can be used to treat effluents from the dyeing process and also to treat the final effluent of textile industries.